2020
DOI: 10.31044/0543-5846-2021-60-55-58
|View full text |Cite
|
Sign up to set email alerts
|

In situ digital image speckle correlation (DISC) observation of plastic strain increment in low-carbon steel

Abstract: The present work is aimed at studying the macroscopic localization of plastic strain in low-carbon steel AISI A283 Grade C. The evolution of macroscopically localized plastic strain at various stages of strain hardening is visualized via a Digital image speckle correlation (DISC) method. The processing of stress-strain curves of the steel samples enabled one to distinguish the following stages of strain hardening: the yield point, the parabolic hardening, and the pre-failure. The inspection of local strain dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The rolling force, as well as the pressing force, is influenced by geometric, mechanical, and physicochemical factors. As Figure 6 shows, geometric factors include slab width and thickness, [ 44,45 ] and the mechanical factor is determined by the internal stress state of the deformation zone, which is related to the width reduction and thickness. The physicochemical factors are represented by the deformation resistanceσ=f(T,u,ε)where T is the deformation temperature, u is a factor determined by the material compositions, ε denotes the deformation degree, which is influenced by the shape of the slab and anvil as well as width reduction.…”
Section: Proposed Modelmentioning
confidence: 99%
“…The rolling force, as well as the pressing force, is influenced by geometric, mechanical, and physicochemical factors. As Figure 6 shows, geometric factors include slab width and thickness, [ 44,45 ] and the mechanical factor is determined by the internal stress state of the deformation zone, which is related to the width reduction and thickness. The physicochemical factors are represented by the deformation resistanceσ=f(T,u,ε)where T is the deformation temperature, u is a factor determined by the material compositions, ε denotes the deformation degree, which is influenced by the shape of the slab and anvil as well as width reduction.…”
Section: Proposed Modelmentioning
confidence: 99%
“…[ 24 ] Hydrogen‐based reduction techniques are at the verge of widespread technical adoption, with solid‐state direct reduction [ 23,25–27 ] already proven at industrial scale (e.g., through the Circored process [ 28 ] ) and the emerging hydrogen plasma reduction (HyPR) [ 29–33 ] (pilot stage) as the most relevant processes. The latter is especially interesting from an energy efficiency standpoint, [ 34 ] where Fe ore is molten and reduced in one step in a modified arc melting furnace under only small partial pressures of hydrogen (e.g., 10% H 2 ), [ 29,30,35 ] ideally produced with renewable energy. While investigating the fundamental reduction reactions over HyPR, it was revealed that almost all accompanying elements brought in with the ore decrease in concentration, resulting in exceptionally pure Fe as the basis for steel production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these technologies, zinc flake coatings are increasingly being used in several markets including automotive, renewable energy and construction industries. [ 1–4 ]…”
Section: Introductionmentioning
confidence: 99%